2017
DOI: 10.1371/journal.pone.0174535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of embryo-derived exosomes on the development of bovine cloned embryos

Abstract: The developmental competence of in vitro cultured (IVC) embryos is markedly lower than that of their in vivo counterparts, suggesting the need for optimization of IVC protocols. Embryo culture medium is routinely replaced three days after initial culture in bovine, however, whether this protocol is superior to continuous nonrenewal culture method under current conditions remains unclear. Using bovine somatic cell nuclear transfer (SCNT) embryos as the model, our results showed that compared with routine renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 52 publications
8
90
0
6
Order By: Relevance
“…The effective dosage of melatonin in vitro was higher than its concentration in vivo; thus, we speculated that other important factors, such as EVs in oviduct fluid, are positively associated with melatonin function. In our previous study, we found that embryos can secrete EVs, which are essential for blastocyst formation and paracrine communication . In this study, we found that EVs exist in the ZP—consistent with a previous study—and that EVs derived from oviduct fluid are distributed on the surface of embryos, suggesting a physical interaction between EVs and embryos.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effective dosage of melatonin in vitro was higher than its concentration in vivo; thus, we speculated that other important factors, such as EVs in oviduct fluid, are positively associated with melatonin function. In our previous study, we found that embryos can secrete EVs, which are essential for blastocyst formation and paracrine communication . In this study, we found that EVs exist in the ZP—consistent with a previous study—and that EVs derived from oviduct fluid are distributed on the surface of embryos, suggesting a physical interaction between EVs and embryos.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study, we found that embryos can secrete EVs, which are essential for blastocyst formation and paracrine communication. 24,43 In this study, we found that EVs exist in the ZP-consistent with a previous study 44 -and that EVs derived from oviduct fluid are distributed on the surface of embryos, suggesting a physical interaction between EVs and embryos. Notably, oviduct fluid-derived EVs decreased ROS, 5-mC, DNMT1, and DNMT3a levels and increased the blastocyst rate of embryos in the in vitro experiments.…”
Section: Discussionsupporting
confidence: 91%
“…A communication between embryos and maternal uterine milieu through secreting signals is required for proper mammalian development (O'Neill, ). Recent studies observed that EVs are secreted from various somatic cells including human embryonic stem cell (Mardpour et al, ), induced pluripotent stem cell (Bobis‐Wozowicz et al, ), ovarian follicle (da Silveira et al, ), and even embryos (Qu et al, ). Our previous study also demonstrated that membrane budding microvesicles from outgrowth embryos improved developmental competence in vitro and the implantation potential of cocultured embryos in utero as well (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not provide data on how many EVs are adding or any quantitative measurement. According to previous studies, they calculated the concentration of EVs in the embryo culture medium by the equivalent of single embryos (Qu et al, ; Saadeldin, Kim, choi, & Lee, ). Saadeldin et al, () extracted 30 μl of exosomes/microvesicles (EXs/MVs) from 125 cloned porcine embryos.…”
Section: Discussionmentioning
confidence: 99%
“…While investigating how these effects were mediated, the conditioned medium obtained from the SCNT embryos was shown to contain exosome sized vesicles that were positive for CD9, a classic EV marker. Interestingly, when these exosomes were added to embryos that were having their growth medium regularly replaced, a noticeable improvement in the health and development of the embryos was observed …”
Section: Introductionmentioning
confidence: 99%